IMPACT OF DIFFERENT STOCKING RATIOS TOTAL FISH PRODUCTION IN FARM PONDS - SHARMA, PAWAN KUMAR; KUMAR, J STEPHEN SAMPATH; MANIKANDAVELU, D.; KUMAR, V. SENTHIL; ANAND, S. (Journal of the Inland Fisheries Society of India, 2026)
This experiment has been carried out under TN-IAMP (Tamil Nadu- Irrigated Agriculture Modernization Project, financed by World Bank) in two selected farm ponds (T1 and T2) of the delta district of Tiruchirappalli (Latitude ‘10.775632’N and Longitude ’78.692360’E) in Tamil Nadu, India, coming under the research and technical purview of Directorate of Sustainable Aquaculture, Thanjavur. The research work was conducted for a period of 270 days. The ponds are of uniform size (0.25 ha), and feature-wise similar in every respect. Both ponds were stocked uniformly with four species combination viz. Catla catla, Labeo rohita, Cirrhinus mrigala, and Cyprinus carpio. The ponds were stocked at the rate of 18000 nos ha-1 maintaining a stocking ratio of 1:1:1:1 (rohu, catla, mrigal and common carp) in T1, while in T2 the ratio was kept at 1.5:1:1:1. Feeding was done twice at 10.00 am and 5.00 pm, with commercial pellet feed (20% crude protein) during the culture period. The estimated gross production in pond T1 (4000kg ha-1) was found to be higher than that of T2 (3200 kg ha-1). The pond T1, has rendered a net estimated additional 800.04kg ha-1, accounting 25.33% higher yield than that of T2 pond. Statically significant (p<0.05), higher survival could be observed in T1 (27.68%) than that of T2 (16.69%). Further, the ADG (Average Daily Growth) rate of fishes in T1 was 25.30% higher than that of T2. This study revealed that there is a tangible correlation between the equal stocking ratio of fishes and production. The survival rate also endorsed this trend.